2023
DOI: 10.3171/case23154
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of spastic foot drop among 16 patients undergoing electrodiagnostic studies: patient series

Abstract: BACKGROUND Differentiating foot drop due to upper motor neuron (UMN) lesions from that due to lower motor neuron lesions is crucial to avoid unnecessary surgery or surgery at the wrong location. Electrodiagnostic (EDX) studies are useful in evaluating patients with spastic foot drop (SFD). OBSERVATIONS Among 16 patients with SFD, the cause was cervical myelopathy in 5 patients (31%), cerebrovascular accident in 3 (18%), hereditary spastic paraplegia in 2 (12%), multiple sclerosis in 2 (12%), chronic cerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Lumbar MRI [1][2][3]8] Knee MRI (if Baker's cyst is palpated or suspected) [4,8,9] EMG/NCV of the lower extremities [3,4,[6][7][8][9][12][13][14][15]18] Ultrasound [3,9] Laboratory studies: total creatine kinase [1,2,12] Cervical/thoracic MRI [1,19] Ankle MRI [1] Muscle biopsy [1] [12]. The patient complained of a 40-year history of chronic right leg pain.…”
Section: Diagnostic Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lumbar MRI [1][2][3]8] Knee MRI (if Baker's cyst is palpated or suspected) [4,8,9] EMG/NCV of the lower extremities [3,4,[6][7][8][9][12][13][14][15]18] Ultrasound [3,9] Laboratory studies: total creatine kinase [1,2,12] Cervical/thoracic MRI [1,19] Ankle MRI [1] Muscle biopsy [1] [12]. The patient complained of a 40-year history of chronic right leg pain.…”
Section: Diagnostic Testsmentioning
confidence: 99%
“…Several studies have reported nerve compression due to a Baker's cyst [3,4,6,[13][14][15][16][17]19,20] (Table 4). Of the 12 reported cases with tibial or both tibial and peroneal nerve compression, the compression involved the former in eight cases and the latter in four cases.…”
Section: Diagnostic Testsmentioning
confidence: 99%